HUBUNGAN LITERASI DIGITAL DAN LEARNING LOSS TERHADAP KEMAMPUAN BERPIKIR FUNGSIONAL PESERTA DIDIK - Hilmina Rofa’ Baedowi; Wiwin Astuti; Suyatman Suyatman; Ari Wibowo (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT The rapid development of digital technology and the emergence of the learning loss phenomenon in the post-pandemic era have become significant challenges in mathematics education, particularly in developing students’ functional thinking skills. This study aimed to analyze the relationship between digital literacy and learning loss with junior high school students’ functional thinking abilities. The study employed a quantitative approach with a correlational research design. The population consisted of all eighth-grade students of MTsN 1 Klaten in the 2025/2026 academic year, totaling 198 students. The sample was selected using a cluster random sampling technique, resulting in two classes with a total of 67 students. Data were collected through a functional thinking test, a digital literacy test, and a learning loss questionnaire. The data were analyzed using descriptive statistics, normality testing, and Spearman Rank nonparametric correlation analysis. The findings revealed that digital literacy did not have a significant relationship with students’ functional thinking abilities. In contrast, learning loss showed a significant negative relationship with functional thinking, indicating that lower levels of learning loss were associated with better functional thinking abilities. These findings suggest that the quality of learning experiences plays a more dominant role than digital literacy in supporting the development of students’ mathematical thinking skills. ABSTRAK Perkembangan teknologi digital dan munculnya fenomena learning loss pascapandemi menjadi tantangan penting dalam pembelajaran matematika, terutama terkait pengembangan kemampuan berpikir fungsional peserta didik. Penelitian ini bertujuan menganalisis hubungan antara literasi digital dan learning loss dengan kemampuan berpikir fungsional peserta didik sekolah menengah pertama. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Populasi penelitian meliputi seluruh peserta didik kelas VIII MTsN 1 Klaten tahun ajaran 2025/2026 yang berjumlah 198 peserta didik. Sampel penelitian ditentukan melalui teknik cluster random sampling sehingga diperoleh dua kelas dengan total 67 peserta didik. Pengumpulan data dilakukan menggunakan tes kemampuan berpikir fungsional, tes literasi digital, dan angket learning loss. Data dianalisis menggunakan statistik deskriptif, uji normalitas, dan korelasi nonparametrik Spearman Rank. Hasil penelitian menunjukkan bahwa literasi digital tidak memiliki hubungan yang signifikan dengan kemampuan berpikir fungsional peserta didik. Sebaliknya, learning loss menunjukkan hubungan negatif yang signifikan terhadap kemampuan berpikir fungsional, yang mengindikasikan bahwa semakin rendah tingkat learning loss, maka kemampuan berpikir fungsional peserta didik cenderung semakin baik. Temuan ini menegaskan bahwa kualitas pengalaman belajar memiliki peran yang lebih dominan dibandingkan kemampuan literasi digital dalam mendukung perkembangan kemampuan berpikir matematis peserta didik.